Sex differences in G protein-coupled estrogen receptor-mediated mechanisms in preclinical models of anxiety and fear - Tran, AnBinh S.; Maeng, Lisa Y. (Frontiers in Behavioral Neuroscience, 2025)
Sex differences are well-documented in the prevalence of psychiatric disorders, with anxiety and stress-related conditions more common in women. Growing evidence highlights the role of sex hormones, particularly estradiol (E2), and its receptor mechanisms as contributing factors to this disparity. Estrogen exerts its effects through three main receptors: estrogen receptor alpha (ERα), estrogen receptor beta (ERβ), and the G protein-coupled estrogen receptor (GPER). While the classical receptors ERα and ERβ have been widely studied in the context of fear and anxiety, the role of GPER remains less understood. Moreover, estrogen receptors themselves may be sexually dimorphic, adding complexity to their functional roles. Preclinical research has been valuable in advancing our understanding of these mechanisms; therefore, this review mostly focuses on findings from rodent studies. Here we discuss the influence of sex and E2 on anxiety and fear-related behavior, highlight emerging research on sex differences in GPER modulation of fear and anxiety in mice, rats, and humans, and explore GPER as a potential therapeutic target for anxiety and stress-related disorders.